Breastfeeding knowledge, attitudes and practices among adolescent teenage mothers at Crossroads, Western Cape, South Africa - Ashwehdi, Ahmad (Division of Family Medicine, 2024)
Background: Breastfeeding is important in supporting the normal growth and development of infants and young children. Evidence shows that breastfeeding is protective against infectious diseases such as upper and lower respiratory tract infections, gastrointestinal illnesses, and otitis media, during the infant period. South Africa has a low exclusive breastfeeding rate. Exclusive breastfeeding for the first six months is the best start for health and development. Adolescent pregnancy is detrimental to the health of mother and child and is a common public health problem worldwide. The identification of factors that promote or inhibit breastfeeding behavior is vitally important for the design of evidence-based policies and interventions. Despite the available knowledge of benefits of breastfeeding, this has not translated into practice in South Africa. Objective: This study aimed to investigate breastfeeding knowledge, attitudes, and practices among adolescent mothers at Crossroads, Western Cape, South Africa. Study- Design and Methods: An analytical cross-sectional study was conducted with 77 mothers aged between 16 and 19 years old, attending Crossroads Community Day Centre located in Mitchell's Plain sub-district, Western Cape. A skilled research assistant performed an in-person meeting with each mother in either English or isiXhosa. Closed-ended questions were used to gather information on socio-demographic characteristics, breastfeeding knowledge, attitudes, and practices. Results: The study analyzed the breastfeeding practices and knowledge of 77 mothers, all of whom reported initiating breastfeeding. However, 31.5% reported discontinuation at the time of the interview. Almost sixty percent of the mothers in this study were unemployed. Most of mothers reported that healthcare workers emphasized the importance of breastfeeding and educated them on appropriate breastfeeding practices. However, only 52.8% of mothers practiced exclusive breastfeeding. Most mothers recognized the benefits of breastfeeding for their babies, including reduced respiratory infections (72.6%), increased intelligence (86.7%), and protection from allergies (94.8%). They also acknowledged benefits for themselves, such as preventing breast Breastfeeding knowledge, attitudes and practices among adolescent mothers at Crossroads, Western Cape, South Africa engorgement (79.5%) and lowering the risk of breast cancer (50.0%). However, many mothers were unaware of the benefits of breastfeeding for child spacing (65.5%), and 56.8% of mothers lacked knowledge on breastfeeding and pre-pregnancy weight. The study found a statistically significant difference in mean knowledge scores for breastfeeding benefits to the baby and the mother. Conclusion: The importance of breastfeeding in babies' lives has been established. However, in low-income communities such as Crossroads, knowledge of the benefits of breastfeeding was variable, and the majority did not practice exclusive breastfeeding. it is important to implement promotional and educational programs in these communities to increase awareness of the vital role of breastfeeding in ensuring optimal development of children.